El juego como estrategia para el desarrollo de la convivencia social en niños de 4 a 5 años en la Unidad Educativa “Chillanes”, Provincia Bolívar - Cevallos Lucio, Carmen Pamela (2025)
The present investigation entitled the game as a strategy for the development of social coexistence in children from 4 to 5 years old in the educational unit Chillanes, Bolivar province, which aims to analyze the impact of the game for the development of social coexistence in children, therefore, the game is conceptualized as a fundamental tool in the teaching-learning process which facilitates the acquisition of knowledge and promotes the integral development of children by helping the social, emotional and cognitive development, Through different types of games such as symbolic and rule games that help them to explore the environment, develop their creativity and learn to work as a team. Likewise, coexistence is essential in the development of children, because it teaches them to relate to their environment in an atmosphere of respect and solidarity for this, we have different types of coexistence such as social, family, school and democratic, each one of them is based on respect and tolerance, creating a healthy environment and effective learning. The present study focuses mainly on the social coexistence of children. Through a mixed methodology where qualitative and quantitative elements are combined using a large number of reliable bibliographic sources such as these, journal articles, specialized websites, books and university repositories, the research design is non-experimental, the techniques used are observation and interview, The results obtained in this research project indicate that social coexistence is fundamental in the educational development in order to be able to live in a comfortable and calm environment. In conclusion, this research helps to understand how important social coexistence is, contributing to the academic environment with information to create strategies that help develop this skill in children.